A study on the entrepreneurs in West Coast (South) Sabah registered with MATRADE Sabah / Nurashikin Antari - Antari, Nurashikin (2007)
The purposes of this study are to identify the reasons of small involvement in export market among entrepreneurs in West Coast (South) Sabah registered with MATRADE Sabah, the problems faced by the entrepreneurs in obtaining the grants from MATRADE and to propose recommendations about MATRADE Sabah Services. The target group is the entrepreneurs in West Coast (South) area of Kota Kinabalu, Penampang and Papar that have registered with MATRADE Sabah. This study applied the exploratory research method. Probability Cluster sampling method are used. The respondents are the entrepreneurs consist of exporters and importers, manufacturers or traders and service provider that have registered with MATRADE Sabah. Findings show that the problems of the entrepreneurs are dwindling of raw material, hard to find network partner, foreign rules and regulations, maintaining production and product quality, high logistics cost and competition from low cost producer.